Design and Assessment of a Mobile Health Care Solution for the Military Pediatrician: The DHA Pediatrics App. Issue 1 (10th June 2021) - Reeves, Patrick T; Royall, Matthew; Spencer, Steven; Rogers, Philip L; Durning, Steven J; Samuel, Anita; O'Meara, Kevin; Gorman, Gregory
ABSTRACT: Introduction: Mobile health technology design and use by patients and clinicians have rapidly evolved in the past 20 years. Nevertheless, the technology has remained in silos of practices, patients, and individual institutions. Uptake across integrated health systems has lagged. Materials and Methods: In 2015, the authors designed a mobile health application (App) aimed at augmenting the capabilities of clinicians who care for children within the Military Health System (MHS). This App incorporated a curated, system-based collection of Clinical Practice Guidelines, access to emergency resuscitation cards, call buttons for local market subspecialty and inpatient teams, links to residency academic calendars, and other web-based resources. Over the next 5 years, three Plan-Do-Study-Act cycles facilitated multiple enhancements for the App which eventually transitioned from the Android/iOS stores to a web browser. The "People At the Centre of Mobile Application Development" tool which has validity evidence captured user experience. The team assessed the App's global effectiveness using Google Analytics. A speed test measured time saved and accuracy of task completion for clinicians using the App compared to non-users. Finally, MHS medical librarians critiqued the App using a questionnaire with validity evidence. The Walter Reed National Military Medical Center Institutional Review Board reviewed the study and deemed it exempt. Results: Clinician respondents ( n = 68 complete responses across six MTFs, 51% graduate medical trainees representing a 7.4% response rate of active duty pediatrician forces) perceived the App to have appropriate qualities of efficiency, effectiveness, learnability, memorability, errors, satisfaction, and cognitive properties following App use in clinical practice. Google Analytics demonstrated more than 1, 000 unique users on the App from May 1, 2020 to January 20, 2021. There were 746 instances (26% of all sessions) when a user navigated between more than one military treatment facility. App users were faster and more accurate at task completion during a digital scavenger hunt. Medical librarians measured the App to have acceptable usefulness, accuracy, authority, objectivity, timeliness, functionality, design, security, and value. Conclusions: The App appears to be an effective tool to extend a clinician's capabilities and inter-professional communication between world-wide users and six MHS markets. This App was designed—and used—for a large health care network across a wide geographic footprint. Next steps are establishing an enduring chain of App champions for continued updates and sharing the App's code with other military medical disciplines and interested civilian centers.